Organisational commitment and employees' personality as predictors of job performance among secondary school teachers in Ido Local Government, Oyo State, Nigeria (2015)
This research examined how organisational commitment and employees' personality could predict job performance of secondary school teachers. The study adopted a survey research design. The participants for the study were 205 (male= 97, female = 108) secondary school teachers from Ido Local Government, Oyo State, Nigeria. Their ages ranged between 22 years and 55 years with the mean age of 38.56 years. Three valid and reliable instruments were used to assess organisational commitment, employees' personality and job performance of teachers. Pearson's product moment correlation and multiple regression analysis were used to analyse the data. The result revealed that organisational commitment and employees' personality were the potent predictors mildly associated with job performance. The study has implications for the employers of labour to take employees' welfare more seriously in order for them to be more productive. Necessary incentives such as conducive working environment, opportunity for career advancement and other monetary incentives should be put in place to motivate the employees to put in their best in their work place.